2012
DOI: 10.2196/med20.1741
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Interventions for Behavior Change and Self-Management: Potential, Pitfalls, and Progress

Abstract: The potential advantages of using the Internet to deliver self-care and behavior-change programs are well recognized. An aging population combined with the increasing prevalence of long-term conditions and more effective medical interventions place financial strain on all health care systems. Web-based interventions have the potential to combine the tailored approach of face-to-face interventions with the scalability of public health interventions that have low marginal costs per additional user. From a patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
150
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(157 citation statements)
references
References 113 publications
(121 reference statements)
3
150
0
4
Order By: Relevance
“…Murray (2012) locates Web-based interventions in three main clinical areas: (1) self-management of long-term conditions (e.g., diabetes, heart disease, arthritis, and asthma), (2) health promotion (e.g., smoking cessation, alcohol reduction, sexual health, diet, and exercise), and (3) mental health (e.g., depression and anxiety). Practically, Medicine 2.0 has been applied in asynchronous and synchronous communication technologies, known as Virtual Healthcare Teams and Disease-Specific Patient Communities, which have achieved high levels of participation.…”
Section: "…Little Has Been Done To Prepare Patients For Long-term Manmentioning
confidence: 99%
“…Murray (2012) locates Web-based interventions in three main clinical areas: (1) self-management of long-term conditions (e.g., diabetes, heart disease, arthritis, and asthma), (2) health promotion (e.g., smoking cessation, alcohol reduction, sexual health, diet, and exercise), and (3) mental health (e.g., depression and anxiety). Practically, Medicine 2.0 has been applied in asynchronous and synchronous communication technologies, known as Virtual Healthcare Teams and Disease-Specific Patient Communities, which have achieved high levels of participation.…”
Section: "…Little Has Been Done To Prepare Patients For Long-term Manmentioning
confidence: 99%
“…A case in point is the comparison between the traditional linear model of clinical/health service research and public health research, driven by the evidence hierarchy [1] (and funding preference) of the Randomised Control Trial (RCT), versus the HCI approach of explorative, rapid iteration and willingness to 'fail quickly'. Questions of risk management, accountability and efficacy are especially pertinent in a health context [2] and highlight the need for a more agile science of digital health.…”
Section: Motivationmentioning
confidence: 99%
“…Several features have been identified that could help to improve adherence to a web-based programme: making the programme tailored to the user and interactive 38 as well as allowing users to set personal goals. 39 Initial withdrawals in this study appeared to have been at the exercise stages of the web programme as there was a higher dropout at stage 2.…”
Section: Non-clinical Study Outcomesmentioning
confidence: 99%